Position, RMB and MMB - Cogorno, Gene R. (McGraw-Hill's AccessEngineering., 2013)
This video illustrates the definition, application, inspection, and the difference between the tolerance of position with datum features specified at regardless of material boundary (RMB) and maximum material boundary (MMB).